Future scenarios of land use change in the Gran Chaco: how far is zero deforestation? - Mosciaro, Maria Jesus (2022)
The Gran Chaco (Argentina, Paraguay, Bolivia and Brazil) has turned into a global deforestation hotspot as a consequence of the agricultural expansion. These land use changes can lead to large socio-ecological conflicts. To reduce adverse effects, common regional planning is needed, which requires diagnostic and prospective information on the territorial dynamics. In this context, we analyzed possible land use change threats over time according to four scenarios of agricultural expansion under different degrees of market opening and state regulation (inertial scenario, high transformation scenario, low transformation scenario, and rigorous law enforcement). Additionally, we identified areas of high susceptibility to deforestation by combining the spatial information from each scenario. We found that the magnitude of the land use changes in the Gran Chaco varies across scenarios, with common spatial patterns of change in the areas adjacent to paddocks previously deforested. This work contributed to a better understanding of the land use change patterns and to envisioning the potential consequences of alternative future land use change scenarios in the Gran Chaco. Particularly, deforestation was analyzed to measure the gap between scenarios and the internationally assumed zero-deforestation objectives. We also identified the areas of greater susceptibility to deforestation where protection efforts should be prioritized when designing future land-use policies and forest governance systems. We demonstrated how scenario generation and simulation models can provide deep insights into the spatiotemporal patterns of deforestation hotspot regions for more sustainable land use planning.